The Role of Counter Narratives in the Renegotiation of Identity - Lyle, Ellyn (Journal of the Canadian Association for Curriculum Studies, 2016)
Teacher identity resides in the foundational beliefs and assumptions educators have about teaching and learning and their participation in these experiences. What happens, though, when these beliefs and assumptions are challenged in such a way that identity is in crisis? Drawing from the literature of personal identity theory, I situate identity as a narrative construct to examine the role of counter narratives in the [re]negotiation of identity.